Pengaruh Kepemimpinan Transformasional terhadap Peningkatan Kualitas Kinerja Pegawai di Dinas Pendidikan Kabupaten Bone Bolango - Podungge, Abdul Wahab (Universitas Gorontalo, 2018)
This study aims to determine the influence of transformational leadership on employee performance in Education Office of Bone Bolango DistrictÂ (Dinas Pendidikan Kab. Bone Bolango). The method used is quantitative, reinforced with the processed statistical data with the dispersion questionnaire. The data obtained came from interviews, observation, literature study, and documentation. The result of the research shows that there are influence of transformational leadership on the performance of the employees in Education Office of Bone Bolango District as follows: a) There is a direct positive and significant influence simultaneously between transformational leadership variables on employee performance in Education Office of Bone Bolango District . b) There is a direct positive and significant influence between the idealized leadership variable (influence ideal) partially on the performance of employees at Education Office of Bone Bolango District. c) There is a direct positive and significant influence between leadership variables inspiration motivation partially on the performance of employees at the Education Office of Bone Bolango District. d) There is a direct positive and significant influence between leadership variables partial intellectual stimulation on employee performance in Education Office of Bone Bolango District. e) There is a positive and significant direct influence between individual leadership considerations partially on employee performance in Education Office of Bone Bolango District.